Development of Interactive E-Module on Islamic Religious Education Subject Implementation of Independent Curriculum at Schools - Lilik Huriyah; Nurul Atik Hamida; Wahidah Ma'rifatunnisa'; Ruhaizan Baru (Edukasia Islamika, 2022)
This study aims to develop an interactive e-module for Islamic religious education and character as the main subject matter of the role of ulama' who spread Islamic teachings in Indonesia to support the implementation of the independent curriculum for class X SMKN 1 Lamongan so that it can help teachers overcome problems that occur when implementing the independent curriculum in the process. learning Islamic religious education and character. The development model used is the ADDIE model. There are four stages in the ADDIE development procedure which are passed through five stages, namely Analysis, Design, Development, Implementation and Evaluation. The data analysis technique is by calculating the percentage score of the validation assessment and user response. The results showed that the results showed that the development of interactive e-modules on the subject of the role of ulama' propagator of Islamic teachings in Indonesia to support the implementation of the independent curriculum met the very valid criteria from the aspect of display quality, software engineering, implementation, interface, reusable, maintainable with obtained a score of 98.77% in terms of IT. The score in terms of material obtained 96.69%. Meanwhile, in terms of media, it got a score of 98.56%. The results of the student and teacher response tests from the pretest results before the implementation of this interactive e-module, each obtained a score of 96.54% and 94.66%. Then there was an increase in student scores on the posttest with an average value of 89 compared to the pretest.